"Es Como Que no los Conociera": Reunification of Unaccompanied Migrant Youth with Their U.S. Families. (6th January 2022) - Barros-Lane, Liza; Brabeck, Kalina; Berger Cardoso, Jodi Arden
Abstract: Family reunification following migration-related separations is often challenging for immigrant youth as they adjust to their new environment and reacquaint with their caregiver. Scant research has explored the experiences of family reunification specifically for unaccompanied immigrant youth. This study was a secondary analysis to explore the complexities of family reunification through the lens of attachment theory and family systems. Data were collected from 30 youth, six parents, and four school administrators via focus groups and semistructured interviews. Unaccompanied immigrant youth had arrived to the United States in the previous three years from Honduras, El Salvador, Guatemala, or Mexico. Data were analyzed using thematic analysis. Results showed that the youth struggled to reconnect with their parents due to prolonged separations, which contributed to loneliness and feelings of loss. Parent–child attachment disruptions contributed to problems related to relationships among family members, traditional family roles and hierarchies, and new family constellations (e.g., blended families). Results point to the importance of developing interventions to increase trust, empathy, and communication between unaccompanied immigrant youth and their parents.